Respon Ketahanan Beberapa Varietas Cabai Rawit (Capsicum frutescens L.) Terhadap Pemberian NaCl secara In Vitro - Adelia, Lita; Siregar, Luthfi A. M.; Lubis, Khairunnisa (Jurnal Online Pertanian Tropik, 2018)
This study was to determine the resistance of ten cayenne pepper (Capsicum frutescens L.) varieties to salinity stress in viro. This research used completely randomized design with two factors, they were cayenne pepper varieties with 10 varieties of Tetra Hijau, Pedas, Cakra Hijau, Sigantung, Wijaya, Sapade, Sret, Bara, Genie and Hanna 08 and NaCl concentration in growing media with five levels 0 ppm, 2500 ppm, 5000 ppm, 7500 ppm dan 10.000 ppm. The results showed that the variety of cayenne pepper and concentration of NaCl and interaction of both had a significant effect on the crown fresh weight and root fresh weight. Sigantung varieties have the highest average on all observed characters.